TINGGALAN PERANG DUNIA KEDUA DI BIBIR PASIFIK - IRWAN ABBAS (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2021)
This study is the result of research on various historical relics of the second world war found on the island of Morotai. The purpose of this study is to find out how far the attention of historical scientists and observers of historical objects left on this island. This study uses a qualitative approach with historical methods, namely data collection through the stages of heuristics, verification, interpretation, and historiography. Heuristics are stages in the search and collection of sources. Verification is the stage of source criticism, both internally and externally. Interpretation is the stage of interpretation and the last is historiography or historical writing. The findings of this study are that various historical remains of world wars on Morotai Island are becoming increasingly rare. Therefore, efforts are needed to save these historical objects which are feared to be destroyed, and even completely disappear due to changing hands or being misused by certain individuals. If this happens, the Morotai people will lose track of their history. Therefore, it is a recommendation that Morotai Island be made a cultural heritage area on the Pacific Rim so that it is hoped that the objects left behind by WW2 can be protected and saved from extinction, because it is our collective responsibility. As an observer of cultural history, it is time for local history studies to receive special attention so that people can know and understand events that have occurred in their area in the past. Keywords: Flakes, World War 2, Pacific Rim (Morotai)